2022
DOI: 10.1088/1361-6668/ac45a0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of transport mechanisms induced by filament-coupling bridges-network in Bi-2212 wires

Abstract: One of the features unique in Bi-2212/Ag wires is the network of bridges between the filaments formed by grains grown through the Ag matrix during the partial-melt heat treatment process. Although these interconnections favor a redistribution of the current among the filaments allowing high critical current density, they represent a strong electrical coupling between the filaments themself. Such a coupling increases the AC losses, present also in case of charge and discharge of DC magnets, principal applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…only 35 µm higher than the as-drawn (round) filament diameter. The results for our partially-bridged wires are consistent with reports of d eff ∼ d bundle [8] and d eff > d bundle in the literature [14,15]. The higher J c 55 × 18 wires had smaller d eff than the 37 × 18 wires at every twist pitch, despite the 55 × 18 wire having 70% higher J c .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…only 35 µm higher than the as-drawn (round) filament diameter. The results for our partially-bridged wires are consistent with reports of d eff ∼ d bundle [8] and d eff > d bundle in the literature [14,15]. The higher J c 55 × 18 wires had smaller d eff than the 37 × 18 wires at every twist pitch, despite the 55 × 18 wire having 70% higher J c .…”
Section: Resultssupporting
confidence: 92%
“…The intrinsic hysteretic losses of the individual filaments may also be enhanced by physical inter-filament 'bridging', where grain-to-grain contacts between neighboring filaments provide superconducting paths for screening currents that shield the enclosed matrix [8]. In the presence of bridging Q t becomes Q t = Q e ( Ḣ) + Q b (ln( Ḣ)) + Q h (ln( Ḣ)), where Q b is the loss component due to bridging and Ḣ = dH/dt is the field sweep ramp rate.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in figure 2, in the best case d eff (4.2 K) mildly decreases with increasing field (35%-37% of d Bundle ), whereas stronger changes are observed in the other two cases (55%-62% and 51%-59% of d Bundle ). A similar decreasing d eff trend was previously found in a different type of Bi-2212 wires in [35], where the investigation was performed in a wider temperature range. The authors found a strong difference in d eff depending on the wire quality and architectures (d eff (10 K, 4-7 T) ∼70%-80% d Bundle in the best case), but also observed a clear temperature dependence with d eff approaching the filament size at higher temperature (>20-25 K) and increasing toward d Bundle with decreasing temperature.…”
Section: Effective Filament Diametersupporting
confidence: 85%
“…As a matter of fact, the magnetic moment of HB samples is close to that of the LB samples in the low magnetic field, while the distinction was intensified with the increase of magnetic fields, as shown in figure 4(a). The effective diameters of HB and LB samples were calculated based on equation (1) [15]. The corresponding results are given in figure 4(b).…”
Section: Resultsmentioning
confidence: 99%
“…However, high-temperature heat treatment result in intense atom diffusion, which also leads to the appearance of bridges between filaments in the Bi-2212 wires [14]. According to previous research, the formation of the bridges could lead to changes in the effective diameter on the basis of the Bean model [15]. The bridges were thought to be hyper channels for current conducting which could be beneficial to increase the critical current.…”
Section: Introductionmentioning
confidence: 99%